Protection against SHIV-KB9 Infection by Combining rDNA and rFPV Vaccines Based on HIV Multiepitope and p24 Protein in Chinese Rhesus Macaques - Chang Li; Zhenwei Shen; Xiao Li; Jieying Bai; Lin Zeng; Mingyao Tian; Ying Jin Song; Ming Ye; Shouwen Du; Dayong Ren; Cunxia Liu; Na Zhu; et al. (Clinical and Developmental Immunology)
Developing an effective vaccine against HIV infection remains an urgent goal. We used a DNA prime/fowlpox virus boost regimen to immunize Chinese rhesus macaques. The animals were challenged intramuscularly with pathogenic molecularly cloned SHIV-KB9. Immunogenicity and protective efficacy of vaccines were investigated by measuring IFN-γ levels, monitoring HIV-specific binding antibodies, examining viral load, and analyzing CD4/CD8 ratio. Results show that, upon challenge, the vaccine group can induce a strong immune response in the body, represented by increased expression of IFN-γ, slow and steady elevated antibody production, reduced peak value of acute viral load, and increase in the average CD4/CD8 ratio. The current research suggests that rapid reaction speed, appropriate response strength, and long-lasting immune response time may be key protection factors for AIDS vaccine. The present study contributes significantly to AIDS vaccine and preclinical research.